Distributed Path Computation with Intermediate Variables (DPCIV) for Distributed Routing Algorithms to Guarantee Routing Decisions - Nishad, KV; Vadivel, R (International Journal of Computer Sciences and Engineering, 2020)
Distributed routing algorithms can lead to a temporary elevation between path regeneration, which can cause major stability problems in high-speed networks. This paper introduces a new algorithm, Distributed Path Computing with Intermediate Variables (DPCIV), which can be integrated with any distributed algorithm to ensure that the directed graph caused by route decisions is always acyclic. An important contribution of DPCIV, in addition to its ability to work with any routing algorithm, is the update method using simple message exchanges between neighboring locations that ensure maximum ease at all times. DPCIV apparently outperforms existing loop blocking algorithms in key metrics such as the frequency of synchronized refresh and the ability to save paths during the transition. The simulation results that block these advantages in the context of a very short path are presented. In addition, the universal performance of DPCIV is demonstrated by studying its use of a functionally-oriented non-shortcut. In particular, the route seeks to counteract the power of failure by increasing the number of subsequent hops available at each destination.